Reclaiming Zakat as an Emancipatory Praxis: A Maqāṣid al-Sharī'ah-Based Reflection on Agricultural Justice and Farmer Welfare in Postcolonial Indonesia - Muhammad Anwar Sani (Tribakti: Jurnal Pemikiran Keislaman, 2025)
This study aims to reposition zakat not merely as a philanthropic tool within the framework of modern economic rationality, but as an emancipatory praxis rooted in the ethical and spiritual values of Islam. In the context of Indonesia's postcolonial agrarian economy-still marked by structural inequality, marginalization of small farmers, and market domination-zakat is conceptually explored as a means of economic decolonization. Guided by the framework of maqāṣid al-sharī'ah and analyzed through the Analytical Network Process (ANP) method, the research examines how zakat-based agricultural programs conducted by several Lembaga Amil Zakat (LAZ), such as Daqu Agrotechno Daarul Qur'an, Dompet Dhuafa, and LAZ Al-Azhar, embody transformative potential in supporting farmer welfare (falah). The central research question asks: to what extent can zakat, through the principles of maqāṣid al-sharī'ah, function as a strategic tool for agrarian justice in postcolonial Indonesia? The study reveals that each LAZ prioritizes different maqāṣid principles, reflecting their respective philosophical orientations-spirituality (ad-dīn) for Daqu Agrotechno, intellectual empowerment (al-'aql) for Dompet Dhuafa, and economic independence (al-māl) for LAZ Al-Azhar. Nonetheless, when all respondent preferences are synthesized, the protection of family and lineage (an-nasl) emerges as the most important dimension (23.10%), followed by economic well-being (22.30%) and religious values (21.60%). The ANP model used in this research recorded high consistency across all decision inputs (inconsistency range: 0.00000 to 0.07103), reinforcing the validity of the findings. Overall, the research demonstrates that zakat, when reclaimed through a maqāṣid-based epistemology, can serve as a critical Islamic response to structural agrarian injustices, redefining development.